Successful conservative treatment of type A aortic intramural hematoma with typical CT evolution: a case report - Wu, Jinlin; Song, Jiayu; Liu, Jie (Frontiers in Cardiovascular Medicine, 2025)
Type A aortic intramural hematoma (IMH) is a variant of acute aortic syndrome, with emergency surgery traditionally considered the treatment of choice. We report a case of a 69-year-old male patient who presented with chest pain. Computed tomography angiography (CTA) revealed type A aortic intramural hematoma. Given the absence of high-risk progression factors, conservative management with close surveillance was selected. During treatment, periaortic hematoma developed in the descending aorta, but the patient's symptoms significantly improved. Follow-up CTA at 3 months demonstrated complete resolution of the intramural hematoma, and the patient remained in good condition at 2.5 years of follow-up. This case demonstrates that conservative treatment may be a viable option for highly selected type A IMH patients without high-risk progression factors, but should only be considered with rigorous patient selection criteria and intensive monitoring protocols in experienced centers.